Cukrzyca u kobiet menopauzalnych - Grzegorz Stachowiak; Tomasz Stetkiewicz; Tomasz Pertyński (Menopause Review, 2011)
Diabetes pathogenesis in the menopausal period is influenced by many factors – e.g. the ageing process and absolute postmenopausal hypoestrogenism. The increasing frequency of glucose metabolism disorders – including IGT and type 2 diabetes mellitus (T2DM) – requires implementation of comprehensive menopausal care, focused on prevention of metabolic and cardiovascular effects of diabetes, requiring close cooperation between the gynaecologist and the diabetologist. Proper use of menopausal hormone therapy (MHT) can be an important element of such care.